Assessments of concentrations of sulfur dioxide (SO2) In Universiti Tun Hussein Onn Malaysia (UTHM) Campus Area, Batu Pahat - Mohd Anuar, Farrah Nuramanina; Othman, Norzila; Altowayti, Wahid Ali Hamood (2021)
More air contaminants have an effect on public health. In recent decades, the topic of production of air pollutants has gained a lot of public interest and research attention. One of the main gases responsible for air pollutants is sulphur dioxide (SO2). The purpose of this research is to explore sulphur dioxide differences at various locations in the campus area of Universiti Tun Hussein Onn Malaysia (UTHM). For this purpose, air pollutant data from thirteen areas were measured at different times. The maximum levels of sulphur dioxide were recorded in the afternoon and the minimum in the morning. SPSS study (one-way ANOVA) of the SO2 concentration at various locations in UTHM revealed eight independent groups for all locations at p<0.5. The highest concentration of SO2 were recorded at KKTDI (a) with the reading of 0.198 and the lowest concentration of SO2 reading were at PKU with the reading of 0.03 ppm. The results of this investigation show that SO2 concentrations are strongly associated to locations near emission sources and have a significant fluctuation in the atmosphere.